Discrimination between Inflammatory and Fibrotic Activity in Crohn's Disease-Associated Ileal-Colonic Anastomotic Strictures by Combined Ga-68-FAPI-46 and F-18-FDG-PET/CT Imaging - Beck, Michael; Kuwert, Torsten; Atzinger, Armin; Gerner, Maximilian; Hartmann, Arndt; Saake, Marc; Uder, Michael; Neurath, Markus; Atreya, Raja (Visceral Medicine, 2024)
Introduction: The development of an intestinal stricture in patients with Crohn s disease represents an important and frequent complication, reflecting the progressive nature of the disease. Depending on the inflammatory and fibrotic composition of the stricture, intensified medical therapy, interventional endoscopy, or surgical intervention is required. However, currently available diagnostic approaches can only assess the level of inflammation, but not the degree of fibrosis, limiting rational therapeutic management of Crohn s disease patients. Recently, prolyl endopeptidase fibroblast activating protein (FAP) has been functionally implicated in fibrotic tissue remodelling, indicating it as a promising target for detection of sites of fibrotic tissue remodelling. Thus, intestinal fibrosis might be visualized using Gallium-68 labelled inhibitors of FAP (FAPI). While F-18-fluorodeoxyglucose (FDG)-positron emission tomography (PET)/CT is a standard diagnostic tool for visualizing inflammatory processes, we combined Ga- 68-FAPI-46-PET/CT and F-18-FDG-PET/CT to differentiate predominantly fibrotic or inflammatory areas in Crohn s disease patients with ileo-colonic strictures. Methods: In our study, we analysed three Crohn s disease patients with anastomotic ileo-colonic strictures who underwent both dynamic Ga-68-FAPI-46-PET/CT and static F-18-FDG-PET/CT imaging to assess the level of visualized fibrotic areas within the stricture and differentiate it from inflammatory ones. PET images were analysed both visually and quantitatively. Furthermore, conventional MR enterography and endoscopy were performed in parallel to correlate observed findings. Two of the included patients underwent surgery and the histological specimen were analysed for the level of inflammation and fibrosis, which results were similarly compared to the findings of the PET imaging procedures. Results: Different uptake patterns of Ga-68- FAPI-46 could be observed in the anastomotic ileo-colonic strictures of the examined Crohn s disease patients, respectively. Immunohistochemical analyses demonstrated that there was a correlation between the level of Ga-68- FAPI-46 uptake and severity of fibrosis, while FDG uptake correlated with the inflammatory activity in the analysed strictures. Discussion: The combination with F-18-FDGPET/CT represents a promising imaging modality to distinguish inflammation from fibrosis and guide subsequent therapy in stricturing Crohn s disease patients, warranting further studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Crohn s disease; FAPI-PET/CT; Fibrosis; Ga-68-FAPI-46; Strictures

Naldemedine versus placebo in opioid-induced constipation: a meta-analysis - Wobbe, Bastian; Gerner, Maximilian; Koehne, Claus-Henning (BMJ Supportive & Palliative Care, 2022)
ObjectiveOpioid-induced constipation (OIC) is a frequent adverse event among patients receiving chronic pain therapy that is requiring opioids. Naldemedine was approved by the Food and Drug Administration to treat OIC and appears to be more efficient than any other peripherally acting mu-opioid receptor antagonist. This meta-analysis aimed at assessing the available data on naldemedine in terms of efficacy. MethodsWe searched the Cochrane Library, PubMed and ClinicalTrials on 24 May 2022 to identify randomised controlled trials (RCTs) comparing naldemedine to placebo among patients reporting OIC. ResultsEvaluation of 6 RCTs enrolling 2769 participants showed significantly greater respondence to treatment (OR=2.48; 95% CI: 2.02 to 3.06; p<0.00001), change in weekly spontaneous bowel movements (SBMs) (mean difference=1.45; 95% CI: 1.14 to 1.76; p<0.00001), complete SBMs (mean difference=0.89; 95% CI: 0.62 to 1.17; p<0.00001) and SBMs without straining (mean difference=0.89; 95% CI: 0.61 to 1.17; p<0.00001) for patients treated with naldemedine. We found no difference in numeric pain rating scales after one (mean difference=0.05; 95% CI: -0.22 to 0.31; p=0.73) and two weeks of treatment (mean difference= -0.04; 95% CI: -0.31 to 0.22; p=0.75). Funding and clinical diversity were possible risks of bias. ConclusionsNaldemedine improves a variety of bowel function parameters while preserving analgesia, confirming its efficacy for patients with OIC. However, head-to-head trials are needed to establish naldemedine as treatment of first choice for laxative-refractory OIC. PROSPERO registration numberCRD42022281353.
CRIS-Team WoS Importer:2023-01-13

Neutralizing monoclonal antibodies against SARS-CoV-2 for COVID-19 pneumonia in a rituximab treated patient with systemic sclerosis-A case report and literature review - Yalcin Mutlu, Melek; Taubmann, Jule; Wacker, Jochen; Tascilar, Koray; Fagni, Filippo; Gerner, Maximilian; Klett, Daniel; Schett, Georg; Manger, Bernhard; Simon, David (Frontiers in Medicine, 2022)
Patients with immune-mediated diseases (IMID) such as systemic sclerosis (SSc), who are treated with B cell depleting treatments, are at risk for developing severe COVID-19 due to inadequate humoral immune response. During B cell depletion, therapeutic substitution of neutralizing monoclonal antibodies against the SARS-CoV-2 spike protein (mAbs) might be helpful to prevent severe COVID-19. It has been shown, that in non-IMID patients mABs reduce SARS-CoV-2 viral load and lower the risk of COVID-19 associated hospitalization or death. However, there are limited data on the effect of mAbs in IMID patients after exposure, especially in patients treated with B cell depleting agents. Herein, we report a case of a rituximab treated SSc patient who developed COVID-19 and was successfully treated with a combination of mAbs (casirivimab/imdevimab). With this case we show that IMID patients may benefit from post-exposure administration of mAbs. In our case treatment with neutralizing autoantibodies was safe and a possible contributor in protecting the patient from mechanical ventilation and eventually death. We frame this case within the current evidence from the literature and provide a perspective on the future potential role of mAbs for treating IMID patients suffering from COVID-19.
CRIS-Team WoS Importer:2022-08-26

Review and Analysis of German Mobile Apps for Inflammatory Bowel Disease Management Using the Mobile Application Rating Scale: Systematic Search in App Stores and Content Analysis - Gerner, Maximilian; Vuillerme, Nicolas; Aubourg, Timothée; Messner, Eva Maria; Terhorst, Yannik; Hörmann, Verena; Ganzleben, Ingo; Schenker, Hannah; Schett, Georg; Atreya, Raja; Neurath, Markus; Knitza, Johannes; et al. (JMIR mHealth and uHealth, 2022)
Background: Patients suffering from inflammatory bowel disease (IBD) frequently need long-term medical treatment. Mobile apps promise to complement and improve IBD management, but so far there has been no scientific analysis of their quality. Objective: This study evaluated the quality of German mobile apps targeting IBD patients and physicians treating IBD patients using the Mobile Application Rating Scale (MARS). Methods: The German Apple App Store and Google Play Store were systematically searched to identify German IBD mobile apps for patient and physician use. MARS was used by 6 physicians (3 using Android smartphones and 3 using iPhones) to independently assess app quality. Apps were randomly assigned so that the 4 apps with the most downloads were rated by all raters and the remaining apps were rated by 1 Android and 1 iOS user. Results: In total, we identified 1764 apps in the Apple App Store and Google Play Store. After removing apps that were not related to IBD (n=1386) or not available in German (n=317), 61 apps remained. After removing duplicates (n=3) and apps for congresses (n=7), journals (n=4), and clinical studies (n=6), as well as excluding apps that were available in only 1 of the 2 app stores (n=20) and apps that could only be used with an additional device (n=7), we included a total of 14 apps. The app “CED Dokumentation und Tipps” had the highest overall median MARS score at 4.11/5. On the whole, the median MARS scores of the 14 apps ranged between 2.38/5 and 4.11/5. As there was no significant difference between iPhone and Android raters, we used the Wilcoxon comparison test to calculate P values. Conclusions: The MARS ratings showed that the quality of German IBD apps varied. We also discovered a discrepancy between app store ratings and MARS ratings, highlighting the difficulty of assessing perceived app quality. Despite promising results from international studies, there is little evidence for the clinical benefits of German IBD apps. Clinical studies and patient inclusion in the app development process are needed to effectively implement mobile apps in routine care.
CRIS-Team Scopus Importer:2022-05-20
Keywords: app store; chronic disease; Crohn disease; IBD; IBS; inflammatory bowel disease; mHealth; mobile apps; quality; rating; rating scale; telemedicine; ulcerative colitis; usability

Safety of Naldemedine for Opioid-Induced Constipation–A Systematic Review and Meta-Analysis - Wobbe, Bastian; Gerner, Maximilian; Köhne, Claus Henning (Journal of Pain and Palliative Care Pharmacotherapy, 2024)
Naldemedine is a peripheral acting µ-opioid receptor antagonist approved by the Food and Drug Administration to treat opioid-induced constipation. Concerns about side effects like opioid withdrawal prevent its widespread use, especially for cancer patients. We performed this systematic review and meta-analysis to evaluate existing safety data of naldemedine treating opioid-induced constipation following the PRISMA guidelines. We searched PubMed and the Cochrane Library on April 16th 2024 to identify studies evaluating naldemedine treatment among patients with opioid-induced constipation. Our analysis found no differences between groups comparing naldemedine therapy with placebo-control for treatment-emergent adverse events (OR = 1.06; 95%-CI: 0.91–1.24), serious adverse events (OR = 1.02; 95%-CI: 0.76–1.38). We found no increased risk for opioid withdrawal, while an increased risk for gastrointestinal disorders (OR = 2.08; 95%-CI: 1.72–2.51), particularly higher incidences of diarrhea (OR = 2.44; 95%-CI: 1.81–3.29) and abdominal pain (OR = 3.31; 95%-CI: 2.16–5.06) were found. In the cancer subgroup, treatment-emergent and serious adverse events were more frequent. However, no increased risk for opioid withdrawal was observed. This analysis confirms naldemedine’s overall safety in treating opioid-induced constipation, with manageable gastrointestinal side effects. However, the higher adverse events in cancer patients require further investigation to ensure safe use in this population.
CRIS-Team Scopus Importer:2025-02-04
Keywords: meta-analysis; Naldemedine; opioid receptor antagonist; opioid-induced constipation